Efficacy of caloric vestibular stimulation for the treatment of idiopathic tinnitus - Saatci, Özlem; Yüksel Aslıer, Nesibe Gül; Arıcı Düz, Özge (Journal of Surgery and Medicine, 2020)
Aim: Caloric vestibular stimulation (CVS) induces the activation of several cortical structures and has been utilized as a neuromodulation technique in the treatment of several disorders. This study purposed to investigate whether CVS would be beneficial in the management of idiopathic tinnitus. Methods: Patients with unilateral idiopathic tinnitus were enrolled in the study. CVS with cold water (study group) and body temperature (control group) irrigation were applied to the symptomatic ear. All patients underwent a standard audiometric examination and visual analogue scale (VAS), the tinnitus handicap inventory (THI) and the Beck depression inventory (BDI) were administered. Results: VAS intensity and disturbance values, mean THI and BDI scores did not show any significant changes in the control group. In the study group, a significant improvement in both the tinnitus intensity and disturbance occurred in the first week post-intervention (P<0.001), and a significant decline was observed in median THI and BDI scores as well as the loudness of the tinnitus in the four weeks post-CVS (P<0.001, P<0.001, P=0.004 and P=0.001) respectively). Conclusion: We can conclude that CVS with cold water leads to a significant decline in the intensity of tinnitus and reduction in the loudness of tinnitus, as well as improving THI and BDI scores.